Joanna - Golonka, Joanna (Wydawcnictwo Naukowe UAM, 1994)
In this paper are described the German infinitive groups with „zu”. The author presents first of all the structure of infinitive constructions and the different versions of them. The second part of the article discusses the semantic and functional contexts of infinitive using in German.